The characteristic of obesity intervention studies among school children in Malaysia : a scoping review - Norhasniza Yaacob; Ruzita Abd Talib; Amirah Ismail; Mohd Izwan Mahmud (Penerbit Universiti Kebangsaan Malaysia, 2021)
Obesity among school children has now reached an alarming level in most developing countries, including Malaysia. Thus, numerous strategies to curb the rising of obesity focusing on school children have been taking place. However, this issue management is complex, and a holistic approach is needed to address it comprehensively. This scoping review aimed to identify the characteristics of obesity interventions conducted among school children in Malaysia as a principal recommendation to develop a comprehensive obesity intervention. Arksey and O'Malley’s framework used to guide the scoping review process. Published articles on intervention studies conducted for school children in Malaysia from 2007 to 2020 retrieved based on keyword using the selected electronic and local databases. The NVivo 12 Plus software used to place findings in the systematic framework matric form and evidence tables. The final results reported in descriptive tables. Eighteen studies only reviewed among 3417 extracted articles. Thirteen aspects of the characteristics of the interventions identified. The influence of environmental intervention (family and school communities) on children lifestyle identified as a research gap. Combined environmental interventions and educational guides with technology application recognised as one of the potential components for future obesity intervention design amongst school children.